The problem of ethno-cultural equivalence of a word in the translations of Abay’s poem into the russian language (Eurasian Journal of Philology Science and Education, 2016)
In the modern world, the problem of understanding the ethno-cultural information is exceedingly important, and it is primarily due to the globalization of cultural space. The problem of understanding is now regarded as the implementation of communication between the subjects through a subject-object relationship «man – the text». When understanding a text of foreign culture, an addresser and a recipient of verbal work are appeared to be carriers of different cultures, and this in its turn may lead to misinterpretation in translation. The article under review deals with the problem of translation of ethno-cultural elements. The article highlights the translation of realities – concepts related to material and spiritual culture of a particular nation. The article discusses the poem of Abay, which is full of lexical units with ethno-cultural component
Keywords: realities; free and literal translation; connotative meaning; transliteration; generalization; national colour; elimination of ethnic and cultural specificity.